2015
DOI: 10.7828/jmds.v4i1.855
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Standard Precautions Among Hospital Nurses in Ozamiz City, Philippines

Abstract: Ozamiz City is the center for health and people from nearby places choose to access its health services because of the available amenities for life-threatening conditions. With the increasing incidence of infectious diseases, compliance of nurses with standard precautions (SP) is necessary to control healthcare-associated infections. This study determined the compliance with SP of 100 nurses in two tertiary hospitals in Ozamiz City using a structured questionnaire that passed the Cronbach's alpha reliability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…To the best of my knowledge, studies on the compliance and adherence of nurses to SPs in the Philippines remain underreported. Compliance of nurses to SPs was reported for a single‐site hospital outside Metro Manila (De Vera & Nero, 2020 ; Pasay et al, 2015 ), and in a qualitative inquiry on the facilitators and barriers to infection control among nurses, physicians, and clinical pharmacists (Mitchell et al, 2017 ). However, these studies were conducted before the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of my knowledge, studies on the compliance and adherence of nurses to SPs in the Philippines remain underreported. Compliance of nurses to SPs was reported for a single‐site hospital outside Metro Manila (De Vera & Nero, 2020 ; Pasay et al, 2015 ), and in a qualitative inquiry on the facilitators and barriers to infection control among nurses, physicians, and clinical pharmacists (Mitchell et al, 2017 ). However, these studies were conducted before the COVID‐19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical calculation on the test of significant relationship using the Pearson r correlation coefficient revealed that work experience and compliance to SP are statistically related. This finding is supported by Pasay (2017), who found that nurses with more years of work experience had higher compliance compared to the least experienced. Similarly, this is also consistent with the finding of Fayaz, et al (2014).…”
Section: Resultsmentioning
confidence: 63%
“…It only means that our health workers in birthing facilities are knowledgeable about the safety precautions and they are practicing it. Pasay, et al (2015) conducted the same study among hospital nurses and they yielded the same results. The respondents showed high compliance to standard precautions.Another study of Chan et al, 2002 about the Nurse's knowledge of and compliance with universal precaution in an acute care hospital in Hongkong revealed that a high compliance was reported regarding hand-washing, disposal of needles and glove usage.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation